Tutorials on African Buffalo Optimization for Solving the Travelling Salesman Problem - Odili, Julius Beneoluchi; M. N. M., Kahar; S., Anwar; M., Ali (Penerbit UMP, 2017)
The African Buffalo Optimization is a newly designed metaheuristic optimization algorithm inspired by the migration of African buffalos from place to place across the vast African forests, deserts and savannah in search of food. Being a new algorithm several researchers from different parts of the research world have indicated huge interest in understanding the working of the novel algorithm. This paper presents a practical demonstration of the workings of the African Buffalo Optimization in solving the popular travelling salesman problem. It is our belief that this tutorial paper will be helpful in further introducing the new algorithm and making it user-friendly.